A structural equation modeling of predictive factors of mathematics undergraduates academic achievement - Falebita, Oluwanife Segun; Asanre, Akorede A.; Chibisa, Admire (Frontiers in Education, 2025)
IntroductionMathematics achievement is the level of knowledge, proficiency or skill attained by undergraduates in mathematics, often explained by grade point average or cumulative grade point average. Many factors could either improve or deter this achievement. In this study, we assess the factors that predict the academic achievement of mathematics undergraduates through structural equation model (SEM).MethodsA survey was conducted with a sample of 411 randomly selected undergraduates from the Department of Mathematics in public universities in Southwestern Nigeria who were studying mathematical science or mathematics education. An adapted questionnaire on a 5-point Likert scale hosted online through Google Forms was used for the survey. The data gathered was analyzed through SEM with the aid of SmartPLS 4.ResultsThe factors examined, mathematics self-efficacy, attitude, motivation and study habits, collectively accounted for 59.4% of the observed variance in the academic achievement of mathematics undergraduates. Similarly, self-efficacy and study habits accounted for 47.7% of the observed variance in academic motivation, while study habits, motivation and self-efficacy accounted for 67.8% of the observed variance in academic attitudes.DiscussionAmong the predictors, study habit has the most predictive influence on academic achievement, followed by mathematics self-efficacy and academic motivation, while academic attitude has the least influence on academic achievement. Hence, academics and institutions should develop and implement various instructional interventions, such as mentoring, monitoring programs and feedback supports, to help students improve their study habits and build their mathematics self-efficacy.